Strengthening of panchayats in India: Comparing devolution across states - Empirical assessment 2012-13 - Alok, V.N. (2013)
This article attempts to provide an empirical assessment of the enabling environment created by sub-national governments in India, of the last two decades, for rural local governments (panchayats) inducing the latter to function as institutions of self-governments. The article constructs a panchayat devolution index incorporating pillars of devolution, i.e. functions, finances, functionaries, capacity building of panchayats and accountability of panchayats, besides observing the setting up of constitutionally provided institutions and their functioning. The article also presents six sub-indices of these pillars. To accomplish this a unique data set is constructed for all states and Union Territories by obtaining data from state governments through a wellstructured questionnaire devised for the purpose. Surveys are also conducted in each state and Union Territory to obtain additional data and validate the data received from the respective state government. These data are then used to rank states and Union Territories on various dimensions, devolution and strengthening of panchayats through state. - Reproduced.
Keywords: Panchayat - India; Panchayat